Heat transfer enhancement in a gas–solid suspension flow by applying electric field. (February 2016) - Tada, Yukio; Yoshioka, Shun; Takimoto, Akira; Hayashi, Yujiro
Graphical abstract: Highlights: Heat transfer in a gas–solid suspension flow is enhanced by electric field. Trajectories of hollow glass particles in an electric field were visualized. A theoretical model of EHD gas–solid suspension flow is proposed and tested. Heat transport by particles is the primary mechanism for enhancing heat transfer. The optimum diameter of particles is determined for enhancing heat transfer. Abstract: Enhancing convective heat transfer is important for improving performance of heat exchangers. We studied the enhancement of heat transfer in a gas–solid suspension flow wherein the solid particle motions were controlled using an electric field. In the experiments, hollow glass particles suspended in air flowed vertically upward in a channel confined by parallel-plate electrodes, one of which served as a heat transfer surface. Particle trajectories, temperature profiles in the airflow, and heat transfer rates were measured. A theoretical study was also performed by considering the particle equations of motion, electric charge transfer at the walls, and heat exchange between particles and the gas phase using the particle source in cell model. As the results, we found that Coulomb forces acting on particles caused alternating one-sided motion in the flow direction through contact charging on the wall electrodes. Thus, particles repeatedly collided with both channel walls. Hence, heat transfer was enhanced, primarily due to heat transport by particles across thermal boundary layer at the heated wall. The simulation results of heat transfer rates were compared with the experimental results, and show quantitatively good agreement. On the basis of the results, the optimum particle diameter for enhancing heat transfer was determined by imposing the condition that the thermal relaxation time of a particle is equal to the contact-charging time of the particle on the wall.